Researches of Programs Implementation in Science of the State and Municipal Management - Evgeniy Vladimirovich Ushakov (Управленческое консультирование, 2018)
The article discusses three generations of policy implementation studies and current state of this field. The main approaches, contributions and issues of implementation research are considered. Implementation at present is understood as a space of actions between centralized control of top management level and decentralized work organization of local implementers. Implementation processes are context-sensitive and there are different implementation styles. Substantial contribution of implementation research consists of understanding of implementation structure significance for implementation outcome. Implementation studies are of fundamental importance for administration since it contribute to clarify a «real life» of administration and of governmental decisions execution.